2021
DOI: 10.2147/ceg.s322512
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Patients’ Immunoglobulin E Levels and Difficulty Eradicating Helicobacter pylori

Abstract: Background: Helicobacter pylori is a cause of gastric cancer, and thus the eradication of this bacterium is very important. The success rate of primary eradication has been dramatically increased by the introduction of potassium-competitive acid blockers. However, H. pylori cannot be eradicated in all patients, and the contributing factors need to be clarified. Aim: Because allergy status may be a factor and considering research linking hay fever with eradication failure, the purpose of this study was to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although the success rate of eradication has increased in recent years, some people still struggle to eradicate H. pylori , and this may be due to patient factors. In a previous study, we found that patients with high IgE levels were less likely to achieve eradication, even after taking into account their sensitivity to the antimicrobial agents used for eradication [ 8 ]. This study suggested that patients with allergic diseases may be more likely to experience eradication failure because they tend to have higher IgE levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the success rate of eradication has increased in recent years, some people still struggle to eradicate H. pylori , and this may be due to patient factors. In a previous study, we found that patients with high IgE levels were less likely to achieve eradication, even after taking into account their sensitivity to the antimicrobial agents used for eradication [ 8 ]. This study suggested that patients with allergic diseases may be more likely to experience eradication failure because they tend to have higher IgE levels.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that eradication failure is associated with hay fever in 2016 [ 6 ], with alcohol consumption in female patients in 2019 [ 7 ], and with high IgE levels taking into account antimicrobial susceptibility in 2021 [ 8 ]. Previous studies have thus shown that pollinosis, IgE levels, and alcohol consumption each affect the failure of H. pylori eradication, but the relationship between these factors and their mechanisms has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation